Big data in cloud computing and the related security issues - Zeyad Aljunaedi, Bajes; Bani Younes, Mohammad (International Journal of Engineering and Technology, 2018)
This paper discusses the security issues associated with cloud computing environment. Additionally, big data, Map Reduce and Hadoop environment have also been catered through this research. The use of big data applications is rising over time because of the benefits of managing massive amount of data easily. Both small scale and large scale organizations use the big data application. Furthermore, the solutions of the problems of cloud computing have been discussed along with Hadoop. This security is developing rapidly and it includes security of the information, computer security, security of the network, and data privacy. The use of cloud computing is evident in policies, technologies, controls, and big data tools that are being used currently. The technology of Cloud computing, big data and its applications are going to form the future of science.Â Â